Gross Anatomy of Femur in Royal Bengal Tiger (Panthera tigris) - Tomar, M.P.S. (Indian Journal of Veterinary Anatomy, 2019)
The present study was carried out on the femur of five adult tiger skeletons. In tiger, the femur was the longest bone of the appendicular skeleton. It presented a shaft and two extremities. Trochanter major was slightly higher in position than the head. Trochanteric crest was terminated in to a tubercle just below the trochanteric fossa and did not meet the trochanter minor. Larger distal extremity was consisted of trochlea and condyles. The intercondyloid fossa was wide, rough and quadrangular in shape. During morphometry, a nonsignificant difference was noticed in the bone of two hind limbs which may be of biomechanical importance.